The Recommending Courses based on the Similarity of Students’ Preferences - Hachem Alaoui Harouni, Moulay; Hachem, El-Kaber; Ziti, Cherif; Bassiri, Mustapha; Lu, Joan (International Journal of Engineering and Technology, 2018)
To keep students in touch, they need to be caught through proposing different courses similar to the ones they are interested in. The present paper is going to discuss the idea of recommending courses and how it will be applied into student profiles as the result of clustering the books or courses as well as the student preferences. It will illustrate the way the item and student profiles enable to recommend courses in our system.Â Â